(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is stated that the world of plants is an important and active component of the biosphere, their importance in the national economy, medicine and many other fields is shown. Morphological description, distribution, growth environment, and growth areas of each plant are given. The importance of each type is explained.